STRATEGI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS KARAKTER UNTUK MENINGKATKAN MORALITAS SOSIAL SISWA MTS ASH- SHAHIHIYAH ROSEP BLEGA BANGKALAN - Tamam, Badrud; Wibowo, Moh. Ari; Desiyanto, Jatim (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Civic Education (PKn) plays a strategic role in shaping citizens who are characterized, have integrity, and actively participate in community life. However, in many schools, PKn learning still tends to emphasize cognitive aspects so that character values are not optimally internalized. This study aims to describe character-based Civic Education learning strategies and their impact on students’ social morality at MTs Ash-Shahihiyah Rosep Blega Bangkalan. This research employed a qualitative approach with a descriptive design. The research subjects consisted of one Civic Education teacher, the principal, and six students as key informants. Data were collected through participant observation, semi-structured interviews, and documentation, and were analyzed using Miles & Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that active, creative, and innovative learning strategies were consistently implemented through group discussions, case studies, contextual media usage, and ice-breaking activities. The cultivation of values such as mutual cooperation, integrity, and independence significantly improved students’ social awareness, discipline, and sense of responsibility. Students’ social morality developed through the habituation of honesty, fairness, and responsibility, modeled by teachers and supported by the school environment. This study affirms that character-based PKn learning is effective in shaping students’ moral behavior and fostering a participatory classroom climate. The implication of this research is that schools must provide adequate facilities and encourage teachers’ innovation in designing character-based learning strategies to ensure that learning outcomes are not only cognitive but also character-building, in line with the Profile of Pancasila Students. ABSTRAKPendidikan Kewarganegaraan (PKn) memiliki peran strategis dalam membentuk warga negara yang berkarakter, berintegritas, dan berpartisipasi aktif dalam kehidupan bermasyarakat. Namun, di beberapa sekolah, pembelajaran PKn masih cenderung menekankan aspek kognitif sehingga nilai-nilai karakter belum terinternalisasi secara optimal. Penelitian ini bertujuan mendeskripsikan strategi pembelajaran PKn berbasis karakter dan dampaknya terhadap moralitas sosial siswa di MTs Ash-Shahihiyah Rosep Blega Bangkalan. Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif. Subjek penelitian meliputi guru PKn, kepala sekolah, dan enam siswa sebagai informan. Data dikumpulkan melalui observasi partisipan, wawancara semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles & Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi pembelajaran aktif, kreatif, dan inovatif diterapkan secara konsisten melalui diskusi kelompok, studi kasus, penggunaan media kontekstual, dan ice breaking. Penerapan nilai gotong royong, integritas, dan kemandirian terbukti meningkatkan kepedulian sosial, kedisiplinan, serta tanggung jawab siswa. Moralitas sosial siswa berkembang melalui pembiasaan nilai kejujuran, keadilan, dan tanggung jawab yang diteladankan guru dan didukung lingkungan sekolah. Penelitian ini menegaskan bahwa pembelajaran PKn berbasis karakter efektif membentuk perilaku moral siswa dan menciptakan suasana kelas yang partisipatif. Implikasi penelitian ini adalah pentingnya sekolah menyediakan dukungan fasilitas dan mendorong inovasi guru dalam mengembangkan strategi pembelajaran karakter sehingga hasil belajar tidak hanya bersifat kognitif, tetapi juga membangun karakter sesuai Profil Pelajar Pancasila.